Adaptive Finite-Time Congestion Control for Uncertain TCP/AQM Network with Unknown Hysteresis. (27th July 2020) - Zheng, Weimin; Li, Yanxin; Jing, Xiaowen; Liu, Shangkun
Abstract : The issue of adaptive practical finite-time (FT) congestion control for the transmission control protocol/active queue management (TCP/AQM) network with unknown hysteresis and external disturbance is considered in this paper. A finite-time congestion controller is designed by the backstepping technique and the adaptive neural control method. This controller guarantees that the queue length tracks the desired queue in finite-time, and it is semiglobally practical finite-time stable (SGPFS) for all the signals of the closed-loop system. At last, the simulation results show that the control strategy is effective.